Tracking cognitive impairment in multiple sclerosis using the Brain on Track test: a validation study - Ruano, L (2020)
Background: The accurate and regular monitoring cognitive performance in multiple sclerosis (MS) patients is critical to develop new prevention and management strategies for cognitive impairment (CI). The Brain on Track (BoT) test is a self-administered web-based tool developed for cognitive screening and monitoring. The objective of this study was to validate the use of the BoT in MS, by assessing its ability to distinguish between MS patients and matched controls, as well as detect CI among MS patients, by analysing its correlation with standard cognitive tests and its reliability and learning effects in repeatable use. Methods: The BoT was applied in 30 patients with MS consecutively selected and 30 age- and education-matched controls, first in a hospital clinic, under supervision, and then 1 week later from home. After these first two trials, MS patients repeated the test from home every 4 weeks for 3 months. A standard neuropsychological battery was also applied to MS patients at baseline. Results: The Cronbach’s alpha was 0.89. Test scores were significantly different between MS patients and controls (Cohen’s d = 0.87; p < 0.01). Among MS patients, scores were significantly lower in those with CI documented in the standard neuropsychological battery than in their cognitively preserved counterparts (Cohen’s d = 2.0; p < 0.001). The BoT scores presented a good correlation with standard neuropsychological tests, particularly for information processing speed. Regarding test–retest reliability, 10/11 subtests presented two-way mixed single intraclass consistency correlation coefficients > 0.70. Conclusion: The BoT showed good neuropsychological parameters in MS patients, endorsing the use of self-administered computerized tests in this setting.